Studi Pengaruh Penggunaan Campuran Abu Fiber Kelapa Sawit dan Semen Untuk Stabilisasi Tanah Lempung - Mildawati, Roza; Hidayat, Rizqi Wahyu (Journal of Infrastructure and Civil Engineering, 2023)
Clay soils are susceptible to changes in moisture content, often experience instability in supporting the load above it, and have a large swelling potential. This study aimed to determine the effect of using palm fiber ash and cement for soil stabilization. This research method is divided into 2 processes of preserving test objects: CBR without soaking (unsoaked) for 0 days and 7 days and CBR soaked (soaked) for 4 days. The mixture variations used were 10%, 15%, 20% palm fiber ash and 7.5% cement. The MDD value was 1.468 g and OMC was 22%. The CBR value without soaking the original soil increased from 10.34% to 18.05% at 7 days of curing. The highest CBR value was obtained in a mixture of 10% palm fiber ash and 7.5% cement at 20.30% at 0 days of curing. The highest CBR value was obtained in a mixture of 10% palm fiber ash and 7.5% cement at 57.34% at 7 days of curing. The soaking CBR value tended to increase from 2.21% to 31.02% in the variation of 20% palm fiber ash and 7.5% cement mixture. The swelling potential value tends to decrease from 0.312% to 0.062%.